Democratização do acesso ao ensino superior: os cursos de graduação à distância na UFRN - Lordsleem, Narcísia Leopoldina Cavalcanti (2011)
This thesis pursuits to contextualize the theoretical debate between the implementation of public education policy of the Federal Government focused in a distance learning and legal foundations for its enforcement, in order to raise questions and comments on the topic in question. Its importance is back to provide scientific input and can offer to the academy, particularly in the UFRN, and elements of society to question and rethink the complex relationship between the socio-economic and geographic access to higher education. It consists of a descriptive study on the institutionalization of distance education in UFRN as a mechanism for expanding access to higher education, for both, the research seeks to understand if the distance undergraduate courses offered by the UAB system and implemented at UFRN, promote expanding access to higher education, as it is during implementation that the rules, routines and social processes are converted from intentions to action. The discussion of this study lasted between two opposing views of Implementation models: Top-down and Bottom-up. It is worth noting that the documents PNE, PDE and programs and UAB MEETING reflect positively in improving the educational level of the population of the country It is a qualitative study, using the means Bibliographic, Document and Field Study, where they were performed 04 (four) in 2010 interviews with the management framework SEDIS / UAB in UFRN. The data were analyzed and addressed through techniques: Document Analysis and Content Analysis. The results show that the process of implementation of distance education at UFRN is in progress. According to our results, the research objective is achieved, but there was a need to rethink the conditions of the infrastructure of poles, the structure of the academic calendar, the management of the SEDIS UFRN, regarding the expansion of existing vacancies and the supply of new courses by the need for a redesign as the Secretariat's ability to hold the offerings of undergraduate courses offered by the Federal Government to be implemented in the institution. It was also found that levels of evasion still presents a challenge to the teaching model. Given the context, we concluded that the greatest contribution of UAB and consequently UFRN by distance learning for undergraduate courses (Bachelor in Mathematics, Physics, Chemistry, Geography and Biological Sciences, beyond the bachelor's degrees in Business and Public Administration ) is related to increasing the number of vacancies and accessibility of a population that was previously deprived of access to university